Manajemen Berbasis Sekolah sebagai Landasan Kepala Sekolah dalam Peningkatan Mutu Pendidikan Agama Islam - Zulfikar Yusuf; Dina Mardiana (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2020)
As a management concept in the field of education management, School Based Management (SBM) was born in the midst of an era of freedom that has emerged since 2004. Through a central government policy that gives flexibility to each education unit in the region to manage their respective institutions. The aims of this article is to analyze: 1) Philosophical foundation of School Based Management (MBS) implementation at SMP Muhammadiyah 4 Malang, 2) The role of school headmaster in improving the quality of Islamic Education at Muhammadiyah 4 SMP Malang. Therefore, this research uses a qualitative approach to the type of case study research. By using observations, interviews and documentation as data collection techniques, this study concludes namely: 1) The philosophical foundation of policy implementation in SMP Muhammadiyah 4 Malang refers to the vision and mission announced by the school, 2) The headmaster of SMP Muhammadiyah 4 Malang has carried out a managerial process well. However, at the evaluation stage there are a number of activities that have not been carried out properly, so that it is unable to locate the shortcomings in the process of the activities carried out.As a management concept in the field of education management, School Based Management (SBM) was born in the midst of an era of freedom that has emerged since 2004. Through a central government policy that gives flexibility to each education unit in the region to manage their respective institutions. The aims of this article is to analyze: 1) Philosophical foundation of School Based Management (MBS) implementation at SMP Muhammadiyah 4 Malang, 2) The role of school headmaster in improving the quality of Islamic Education at Muhammadiyah 4 SMP Malang. Therefore, this research uses a qualitative approach to the type of case study research. By using observations, interviews and documentation as data collection techniques, this study concludes namely: 1) The philosophical foundation of policy implementation in SMP Muhammadiyah 4 Malang refers to the vision and mission announced by the school, 2) The headmaster of SMP Muhammadiyah 4 Malang has carried out a managerial process well. However, at the evaluation stage there are a number of activities that have not been carried out properly, so that it is unable to locate the shortcomings in the process of the activities carried out. Keywords: Leadership, School Based Management, Islamic Education, School Headmaster Abstrak Sebagai sebuah konsep manajemen di bidang pengelolaan pendidikan, Manajemen Berbasis Sekolah (MBS) lahir di tengah-tengah era kebebasan yang telah mengemuka sejak tahun 2004 silam. Melalui kebijakan pemerintah pusat yang memberi keleluasaan pada tiap satuan pendidikan di daerah untuk mengelola lembaganya masing-masing. Tujuan penulisan artikel ini ialah untuk menganalisis: 1) Landasan filosofis implementasi Manajemen Berbasis Sekolah (MBS) di SMP Muhammadiyah 4 Malang, 2) Peran kepala sekolah dalam meningkatkan mutu Pendidikan Agama Islam di SMP Muhammadiyah 4 Malang. Oleh karenanya, riset ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Dengan menggunakan observasi, wawancara dan dokumentasi sebagai teknik pengumpulan data, penelitian ini berkesimpulan antara lain: 1) Landasan filosofis implementasi kebijakan di SMP Muhammadiyah 4 Malang mengacu pada visi misi yang dicanangkan oleh sekolah, 2) Kepala SMP Muhammadiyah 4 Malang telah melakukan proses manajerial dengan baik. Namun, pada tahapan evaluation terdapat beberapa aktivitas yang belum dilakukan proses evaluasi dengan baik, sehingga tidak mampu menemukan letak kekurangan dalam proses kegiatan yang dilakukan. Kata Kunci : Kepemimpinan, Manajemen Berbasis Sekolah (MBS), Pendidikan Agama Islam, Kepala Sekolah